Insights on the Pooled Prevalence and Global Distribution of Leptospirosis in Goats: Systematic Review and Meta-Analysis - Roseane de Araújo Portela; Clécio Henrique Limeira; José Artur Brilhante Bezerra; Camila Marinelli Martins; Diego Figueiredo da Costa; Carolina de Sousa Américo Batista Santos; Clebert José Alves; Sérgio Santos de Azevedo (Microorganisms)
Leptospira spp. infection in small ruminants is usually asymptomatic or presents nonspecific clinical signs and has an economic impact on goat farming and public health. The aim of this study was to carry out a systematic review with meta-analysis on the global seroprevalence and distribution of leptospirosis in goats. The methodology was based on the recommendations of Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA), and the review project was registered in the International Prospective Register of Systematic Reviews (PROSPERO—ID: CRD42023405693). Overall, 79 articles were included in the study. The global prevalence of leptospirosis in goats was 18.6% (CI 95% = 15.08–22.71%), with no publication bias and high heterogeneity. The records originated from South America (n = 32), Asia (n = 26), Europe (n = 8), North America (n = 7), and Africa (n = 6), and seropositivities were 17%, 19%, 12%, 34%, and 22%, respectively. It is concluded that Leptospira spp. infection is widespread in goat herds, including regions with semi-arid and arid climates, and it is suggested that the prospects for controlling the disease should focus on avoiding environmental contamination and improving management measures and sanitary practices. This important information provides guidance for actions to protect against human contamination and to control animal leptospirosis.